Uncertainties of Annual Suspended Sediment Transport Estimates Driven by Temporal Variability - Aron Slabon; Thomas Hoffmann (Water Resources Research)
Abstract The majority of sediment transported from rivers to the global oceans is moved in suspension as fine particles. Thereby, the transported sediment shapes the physical environment regarding erosive and accumulative processes. Temporal variations in sediment supply and transport lead to unquantified uncertainties in annual load estimates, requiring high‐resolution data sets and a sound understanding of site‐specific catchment characteristics. We investigate the temporal variability of suspended sediment transport in four catchments in Germany with highly different discharge regimes and catchment sizes (<1,000 km2 to >100,000 km2). The data set consists of high‐resolution 15‐min turbidity measurements with daily discharge and frequent manual sampling. Utilizing a bootstrap approach based on the 15‐min time series, we assessed the impact of the sampling interval on annual load estimates for less frequent data sets. We use the sediment load exceedance time (Ts80%) as a measure of variability and relate it to uncertainties in annual load estimates. Since low‐frequency data sets rely on sediment rating curves, we performed a sensitivity analysis of the rating parameters a, b, and ε. Our results indicate a negative exponential relationship between Ts80% and uncertainties in annual load estimates. Based on the Ts80%, we can derive the shortest sampling frequency necessary to obtain annual load estimates with an error of <20% over varying discharge regimes. Additionally, Ts80% is linked to rating exponent b, with low b‐values indicating high Ts80%‐values and lower variability, and high b‐values indicating higher variability.